IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM MEMBANGUN KEPUASAN PELANGGAN - Junaidi; Dina Mardiana Nur Hazanah; Lailatus Saadah; Raja Dewantara Putra; Moh. Yunus Agung Prayoga (PT. Hasba Edukasi Mandiri, 2026)
Total quality management (TQM) or integrated quality management describes a focus on quality that drives the entire organization, from suppliers to consumers. TQM becomes a necessity for every company that wants to provide satisfaction to its customers. Talking about TQM is related to the quality that will be delivered to customers. In this case, quality is an activity of continuous improvement carried out to win competition. In addition, quality provides a stimulus for customers to establish a strong relationship with the company. With this quality, customer satisfaction can be increased, where the company can enhance pleasant customer experiences and minimize or eliminate unpleasant customer experiences. Therefore, for the implementation of TQM to achieve success, the company must have clear and directed guidelines so that the company's goals can be achieved.